Jezus Chrystus – Pierworodny w historii dzieciństwa według Łukasza - Kozyra, Józef (Studia Pastoralne, 2026)
The main theme: Jesus Christ The Primogenital as it appeares in the gospel of St. Luke touches the historical and theological problem. As it stands in the Gospels, history is a servant of theology. Very often talking about the history of Jesus’ childhood it is treated as the Gospel of childhood. In the childhood story of St. Luke’s Gospel 1–2 an importent role plays the title Prototokos-Primogenital. It brings to our attention, who Jesus was at hist childhood, shows His place in the history of salvation, shows His relation to God and people. St. Luke presents it in two childhood stories: in chapter 2.1-7 about the birth of Jesus in Betlehem, and in chapter 2.22-24 at the presentation in Jerusalem. In the presentation of this theme firstly was stressed the theological point in the Gospel of St. Luke. The historical facts in the childhood stories are: the census, the place of birth of Jesus, His jewish identity- the circumcision, the giving of the name, the offering at the temple and the pilgrimage to Jerusalem. Further on the narrative goes to the birth in Betlehem, the presentatio at the Temple as a First-Born in the context of verses Luke 1–2. Then follows the christological title Prototokos. This title has been presented as well in the tradition of the Apostolic teaching in the New Testament (Rom. 8.29; Col. 1.15, 18; Rev.1.5 and Heb. 1.6) where this title more than others characterises Jesus Christ as posessing the unity of intentional salvific God’s Will and He posesses it from the beginning of His incarnation, throughout Hist birth, His offering in the Temple, He is indeed the Primogenital of all creation, permanently subordinate to His Fathers Will. In reality and historically He entered our human world.